2012
DOI: 10.1016/j.gloplacha.2012.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Too wet for oaks? Inter-tree competition and recent persistent wetness predispose oaks to rainfall-induced dieback in Atlantic rainy forest

Abstract: Forest dieback is usually triggered by climatic extremes, even if tree decline can be caused by diverse biotic and abiotic stressors acting synergistically on tree vitality. Many case studies worldwide illustrate the global importance of drought-induced forest dieback under a context of climate warming. However, forest decline is also occurring in regions that are not water-limited, but where increasing rainfall and exceptionally rainy events are observed. Here we assessed the influence of inter-tree competiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(26 citation statements)
references
References 60 publications
2
23
1
Order By: Relevance
“…When radial growth of sampled individuals was averaged into a mean stand tree-ring chronology, there is no relationship between the climatic response of mean stand chronology and stand tree density or basal area (results not shown). A previous study in this forest showed that oaks that died, as a consequence of the extremely rainy conditions in the year 2001, were smaller and had lived under higher competition levels than surviving oaks (Rozas & García-González 2012). This evidence supports the theory that competition can predispose trees to the damaging effects of a climatic stress (Linares et al 2010).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…When radial growth of sampled individuals was averaged into a mean stand tree-ring chronology, there is no relationship between the climatic response of mean stand chronology and stand tree density or basal area (results not shown). A previous study in this forest showed that oaks that died, as a consequence of the extremely rainy conditions in the year 2001, were smaller and had lived under higher competition levels than surviving oaks (Rozas & García-González 2012). This evidence supports the theory that competition can predispose trees to the damaging effects of a climatic stress (Linares et al 2010).…”
Section: Discussionsupporting
confidence: 79%
“…The dominant woodland is an Ibero-Atlantic acidophilous oak forest (G1. (Rozas & García-González 2012).…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…An enhancing effect of precipitation is widely observed in the Mediterranean environments (Santini et al, 1994;Tessier et al, 1994;Čufar et al, 2008) and the Atlantic Spain (Rozas, 2001(Rozas, , 2005, where high precipitation creates favourable and high temperature unfavourable growth conditions during the summer period. On the other hand, water excess can be limiting for growth and is triggering forest dieback in rainy temperate deciduous forest (Rozas and García González, 2012). Anyway, the importance of summer precipitation for oak tree-ring width is evident across Europe.…”
Section: Summer Precipitation Signalmentioning
confidence: 99%
“…Temperate trees suffer from additional stress sources at the transitional areas between Atlantic and Mediterranean regions revealing a more complex picture (González-González et al, 2014). For example, high levels of precipitation combined with relatively high winter temperatures has been shown to be the main cause for growth reduction and dieback of Q. robur in the north-western Iberian Peninsula (Rozas & García-González, 2012). Analyses of F. sylvatica tree-ring chronologies from south-western Europe have shown that spring temperature, together with the amount of winter precipitation, coexist with water availability in summer as major drivers of radial growth (Lebourgeois et al, 2005;Piovesan et al, 2005).…”
Section: Fig 1 Distribution Ranges Of the Four Studied Species Of Bmentioning
confidence: 99%